THE FUNCTION OF ISLAMIC RELIGIOUS EDUCATION IN RENEWING CHACATER BUILDING - Ismail, Irfan; Nugraha, Mulyawan Safwandy (INTIHA: Islamic Education Journal, 2024)
This study aims to explore how Islamic religious education influences the formation of individual character with high moral values. Furthermore, character education also aims to enhance the quality of educational outcomes by paying specific attention to develop personalities in line with the education graduate competency standards. Additionally, the goal of character education is to refine ethical intelligence and strengthen moral aspects by cultivating a better understanding of right and wrong things. In conducting this study, the methodology employed was systematic literature review involving gathering information from various literary sources related to the discussed topic. Statistical data utilized in this research was derived from books, research journals, and supporting articles. The research findings indicated that the role of Islamic religious education in enhancing character involved regulating and supervising the younger generation by instilling religious values, faith, piety, knowledge, and good conduct in order to ensure that despite the currents of globalization, the younger generation remains capable of upholding Islamic traditions and applying the positive values derived from the religion.